Implikatur Sindiran pada Debat Presiden Antara Joe Biden dan Donald Trump di Siaran CNN 2024 - Marlina Marlina; Lusi Susilawati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines sarcastic implicatures in the 2024 United States presidential debate between Joe Biden and Donald Trump, with a particular focus on Donald Trump’s utterances. The study aims to identify the forms and types of sarcastic implicatures employed in political discourse during the debate. A qualitative descriptive method with a pragmatic approach was used to analyze how implied meanings are constructed and interpreted within the context of political communication. The data consisted of debate transcripts and video recordings broadcast by CNN, selected based on utterances containing elements of sarcasm. Data analysis was conducted through four stages: identification, classification, coding, and interpretation. The findings reveal that sarcastic implicatures are realized in two main forms, namely indirect non-literal utterances and direct non-literal utterances. In addition, several types of sarcastic implicatures were identified, including undermining, mockery, insult, criticism, and threat. The most dominant type was undermining, which was used to weaken the image and credibility of political opponents. These findings indicate that sarcastic implicatures function as an effective rhetorical strategy in political communication to influence public opinion, shape audience perceptions, and strengthen the speaker’s political position in televised political debates.